Building capacity for professional development: the development of teachers as facilitators in Ghana. Issue 3 (27th May 2019) - Perry, Emily; Bevins, Stuart
ABSTRACT: In low- and middle-income countries, cascade models of teacher professional development are often used as routes to educational reform. In these models, external agents deliver professional development, which is then disseminated by in-country facilitators. However, little is known about how to support facilitators of professional development, particularly in low- and middle-income countries. In this study, we report on a model of capacity building for professional development in Ghana. In the context of a large-scale programme of science teacher professional development, a group of Ghanaian teachers gradually assumed responsibility for professional development facilitation, working alongside experienced facilitators from the UK. Using interviews focussed on a storyline technique, we explore the experiences of the Ghanaian teachers as they reflected on their roles. We found the teachers' epistemological beliefs about teaching were coherent with those of the programme and suggest that this may be an important factor in the success of cascade models of professional development. The teachers gained self-confidence and improved their knowledge and skills of teaching and of professional development facilitation. We propose that this is useful learning for all facilitators and that the model described here is one which is potentially useful for capacity building in other contexts.